Satisfação com a vida, estresse percebido e suporte social em cuidadores informais de pessoas com demência - Moura, Alan Ehrich de (2022)
The task of caring for a person with dementia can be overwhelming due to the myriad needs and associated symptoms. This function, in most cases, is performed by a family member who assumes the role of informal caregiver to the patient. In this scenario, understanding the psychological and social factors that promote well-being in family caregivers is essential for the care of this population. Thus, the objective was to evaluate the interdependent relationships between perceived stress, life satisfaction, social support and mental health in informal caregivers of people with dementia. A cross-sectional descriptive study was carried out with 452 family caregivers (81.9% women), aged between 21 and 89 years (M = 52.3; SD = 11.2), from different regions of Brazil. Participants answered a virtual questionnaire containing specific psychometric scales to measure constructs of the family caregiver and the person with dementia; in addition to sociodemographic and clinical issues. Three theoretical models were implemented through structural equation modeling to explore the interrelationships between the constructs (perceived stress, life satisfaction, social support and mental health), as well as their combined or simultaneous effects. As a result, the models tested showed satisfactory fit indices, giving the models plausibility. When comparing them, Model 1 (which evaluated the mediating effect of social support on the relationship between perceived stress and life satisfaction) fitted the data better. These findings evidenced social support and life satisfaction as alternative targets to improve indicators of psychosocial well-being, health behaviors and mental health outcomes of the caregiver. It is concluded that this work produced information about the protective factors of well-being of informal caregivers that can be used by professionals in the area of health and social assistance to subsidize decisions, in the sense of promoting these factors, providing better living conditions for children. this population.